Oxytocin: an unexpected risk for cardiologic and broncho-obstructive effects, and allergic reactions in susceptible delivering women - Liccardi, Gennaro; Bilò, Maria Beatrice; Mauro, Ciro; Salzillo, Antonello; Piccolo, Amedeo; D’Amato, Maria; Liccardi, Annabella; D’Amato, Gennaro (Multidisciplinary Respiratory Medicine, 2013)
Oxytocin (Sintocynon) is considered an uncommon cause of severe allergic reactions during delivery. We have recently shown that allergic sensitization to latex might constitute an important predisposing risk factor for anaphylaxis after the first infusion of oxytocin during delivery. Some oxytocin cardiovascular activities such as lowering blood pressure, negative cardiac inotropy and cronotropy, parasympathetic neuromodulation, vasodilatation etc. can induce significant side effects mimicking cardiac anaphylaxis, and constitute an additional differential diagnostic problem in delivering women with suspected or real allergic background. Finally, some ex vivo models have shown that oxytocin, under pro-inflammatory cytokines stimulation, such as those occurring in asthma, may induce contraction of smooth muscle and airway narrowing. This background suggests that allergic sensitization to latex allergens constitutes a significant but underestimated risk factor for triggering severe systemic reactions after the infusion of oxytocin and, consequently, there is a need of particular attention in managing delivering women suffering from latex allergy and bronchial asthma. An accurate anamnestic, clinical and diagnostic evaluation, latex-free anesthesiological setting, use of oxytocin-alternative agents and, if necessary, a drug premedication are likely to reduce the risk of anaphylactic/broncho-obstructive reactions in these women.